68.8k views
0 votes
Simplify and solve this equation for q: 3p+5+2p-5=65

User Pmuens
by
5.1k points

2 Answers

4 votes

Explanation:

Let's solve:


3p+5+2p−5=65

Step 1: Simplify both sides of the equation.


3p+5+2p−5=65 \\ 3p+5+2p+−5=65 \\ (3p+2p)+(5+−5)=65(Combine Like Terms) \\ 5p=65 \\ 5p=65

Step 2: Divide both sides by 5.


(5p)/(5) = (65)/(5) \\ p = 13

User Banane
by
5.0k points
1 vote
Eliminate the 5’s because they cancel each other out.
Add 3p + 2p to get 5p
5p= 65
Divide by 5
P = 13
User BAP
by
5.6k points